Cover Picture: Pebax/MWCNTs‐NH2 mixed matrix membranes for enhanced CO2/N2 separation (Greenhouse Gas Sci Technol 2/2020). Issue 2 (23rd April 2020) - Song, Chunfeng; Mujahid, Muhammad; Li, Run; Ahmad, Siraj; Liu, Qingling; Zhang, Bing; Kitamura, Yutaka
Abstract : The cover image is based on the Original Research Article Pebax/MWCNTs‐NH2 mixed matrix membranes for enhanced CO2 /N2 separation by Chunfeng Song et al., https://doi.org/10.1002/ghg.1970 .